The integration of Central and Eastern Europe in the European Union: Trade and labour market adjustment - Erik Faucompret; Jozef Konings; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 1998)
This paper analyses the economics of EU enlargement from three perspectives. First, we provide an institutional background and point out the importance of Agenda 2000. Second, we then analyse the implications for EU trade with Central and Easter European Countries (CEEC's) and in particular we discuss the EU Antidumping legislation and its implications for trade integration between the EU and CEEC's. Third, we engage in an analysis of the implications of economic integration for the EU labour market. To this end, we use a unique firm level survey of 281 Belgian firms. Our findings suggest that: (i) the EU follows a too restrictive approach to trade integration; (ii) economic integration with CEEC's leads to a reduction in the demand for low-skilled labour in small firms, however, this effect is reversed for large firms.
Keywords: 330